As concepções de envelhecimento e velhice nas políticas públicas voltadas à população idosa no Brasil e no Uruguai - Mariño, Juliana de Crescenzo Saucedo (2019)
Public policies can contribute to the reproduction or questioning of stereotypes and stigmas related to old age. This will depend a lot on which conception of aging was considered in the formulation of policy documents. Thus, the main objective of this study is to understand the concept of old age and aging that underlies certain public policy documents aimed at the elderly in Brazil and Uruguay. It is a qualitative study, in which a documentary research was carried out (MAY, 2004) whose content analysis followed the theoretical framework of Bardin (1977). The choice followed a criterion of international and national relevance. Thus, the first document analyzed was the Inter-American Convention on the Protection of the Human Rights of Older Persons (2015). In the case of documents of national scale, the National Policy for the Elderly, the National Health Policy for the Elderly and the Elderly Statute were analyzed by Brazil and by Uruguay, the Según Plan de Envejecimiento y Vejez. Uruguay was chosen because it is currently considered the oldest country in South America, in addition to having signed and ratified the Inter-American Convention on the Protection of the Human Rights of Older Persons. We could see in the analysis that Brazilian documents have as their main theoretical perspective that of active aging. Unlike Uruguay, Brazil adopts Active Aging as the only theoretical approach to support public policy documents, which is the prevailing concept of aging. With this in mind, we ask ourselves: What does it mean to have active aging as the conceptual basis for policies in Brazil? In the case of the analyzed Uruguayan document, we could see that the concept of old age and aging is another. It is based on the Convention, that is, part of the idea that old age is a social construction and that older people are subject to rights, having as a theoretical focus the theory of the course of life, despite some confusions that appear in the text